The meridian Masinag community and commercial hub - Jacosalem, John Paul M.; Santos, Maria Lisa V. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
The City of Antipolo is the capital of the Rizal province, one of the best performing provinces in the country. Consequently, Antipolo City is also among the top component cities in the Philippines. It also boasts of rich products, traditions, culture and experiences that make it a worth a visit and for some people, the stay. All of these serves as an affirmation of Antipolo's slogan "Tayo na sa Antipolo". As part of its development plan, the city has identified six growth centers for 2010 to 2020. Masinag is one of the said growth centers and it is where the project will be located. Due to its proximity to Metro Manila and the presence of Light Rail Transit (LRT) -2 line, it is envisioned to be Antipolo City's Central Business District. Upon analysis of the district, the following agenda have been formulated as a response to the current and future conditions of Masinag: Urban Living, Economic Growth, Community and Connectivity. Guided by these agenda, The Meridian: The Masinag Community and Commercial Hub is proposed. The project will house highly-density residential units, business and retail spaces, a learning commons, tranport facilities, as well as social and congregational public and private spaces. Masinag as a district, hasn't yet achieved the level of intensity of other Central Business Districts. This project then, is envisioned to be a transport-oriented development that will serve as a template for future endeavors in the developing district of Masinag.
Include appendices
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Cities and towns -- Growth; Cities and towns -- Growth -- Philippines